2016
DOI: 10.1117/1.jbo.21.8.085003
|View full text |Cite
|
Sign up to set email alerts
|

Laser-triggered release of encapsulated molecules from polylactic-co-glycolic acid microcapsules

Abstract: The controlled release of encapsulated molecules from a microcapsule is a promising method of targeted drug delivery. Laser-triggered methods for the release of encapsulated molecules have the advantage of spatial and temporal controllability. In this study, we demonstrated the release of encapsulated molecules from biodegradable polymer-based microcapsules using near-infrared femtosecond laser pulses. The polylactic-co-glycolic acid microcapsules encapsulating fluorescein isothiocyanate-dextran molecules were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…This may be due to the different degree of change in the degradation rate depending on the laser wavelength, as described in Section 3. Ariyasu et al reported the burst release of embedded molecules triggered by femtosecond laser pulses [64]. The release of fluorescence molecules encapsulated in biodegradable microcapsules was significantly enhanced by laser irradiation.…”
Section: Laser-triggered Molecular Release From Biodegradable Polymersmentioning
confidence: 99%
“…This may be due to the different degree of change in the degradation rate depending on the laser wavelength, as described in Section 3. Ariyasu et al reported the burst release of embedded molecules triggered by femtosecond laser pulses [64]. The release of fluorescence molecules encapsulated in biodegradable microcapsules was significantly enhanced by laser irradiation.…”
Section: Laser-triggered Molecular Release From Biodegradable Polymersmentioning
confidence: 99%